Predicting the Risk of Disease Recurrence and Death Following Curative-intent Radiotherapy for Non-small Cell Lung Cancer: The Development and Validation of Two Scoring Systems From a Large Multicentre UK Cohort. Issue 3 (March 2021) - Evison, M.; Barrett, E.; Cheng, A.; Mulla, A.; Walls, G.; Johnston, D.; McAleese, J.; Moore, K.; Hicks, J.; Blyth, K.; Denholm, M.; Magee, L.; et al.
Abstract: Aims: There is a paucity of evidence on which to produce recommendations on neither the clinical nor the imaging follow-up of lung cancer patients after curative-intent radiotherapy. In the 2019 National Institute for Health and Care Excellence lung cancer guidelines, further research into risk-stratification models to inform follow-up protocols was recommended. Materials and methods: A retrospective study of consecutive patients undergoing curative-intent radiotherapy for non-small cell lung cancer from 1 October 2014 to 1 October 2016 across nine UK trusts was carried out. Twenty-two demographic, clinical and treatment-related variables were collected and multivariable logistic regression was used to develop and validate two risk-stratification models to determine the risk of disease recurrence and death. Results: In total, 898 patients were included in the study. The mean age was 72 years, 63% (562/898) had a good performance status (0–1) and 43% (388/898), 15% (134/898) and 42% (376/898) were clinical stage I, II and III, respectively. Thirty-six per cent (322/898) suffered disease recurrence and 41% (369/898) died in the first 2 years after radiotherapy. The ASSENT score (age, performance status, smoking status, staging endobronchial ultrasound, N-stage, T-stage) was developed, which stratifies the risk for disease recurrence within 2 years, with an area under the receiver operating characteristic curve (AUROC) for the total score of 0.712 (0.671–0.753) and 0.72 (0.65–0.789) in the derivation and validation sets, respectively. The STEPS score (sex, performance status, staging endobronchial ultrasound, T-stage, N-stage) was developed, which stratifies the risk of death within 2 years, with an AUROC for the total score of 0.625 (0.581–0.669) and 0.607 (0.53–0.684) in the derivation and validation sets, respectively. Conclusions: These validated risk-stratification models could be used to inform follow-up protocols after curative-intent radiotherapy for lung cancer. The modest performance highlights the need for more advanced risk prediction tools. Highlights: Two validated risk prediction models for disease recurrence and death are presented. The performance of the scores are modest. Rates of further curative intent treatment for disease recurrence were low (4%). The majority with disease recurrence were managed with best supportive care (57%). More advanced risk prediction tools and research into optimal follow-up is needed.